Ethyl Pyruvate Induces Tolerogenic Dendritic Cells - Djedovic, Neda; Mansilla, María José; Jevtić, Bojan; Navarro-Barriuso, Juan; Saksida, Tamara; Martínez-Cáceres, Eva M.; Miljković, Ðorđe (Frontiers in Immunology, 2019)
Dendritic cells (DC) are professional antigen presenting cells that have a key role in shaping the immune response. Tolerogenic DC (tolDC) have immuno-regulatory properties and they are a promising prospective therapy for multiple sclerosis and other autoimmune diseases. Ethyl pyruvate (EP) is a redox analogue of dimethyl fumarate (Tecfidera), a drug for multiple sclerosis treatment. We have recently shown that EP ameliorates experimental autoimmune encephalomyelitis, a multiple sclerosis murine model. Here, we expanded our study to its tolerogenic effects on DC. Phenotypic analysis has shown that DC obtained from mice or humans reduce expression of molecules required for T cell activation such as CD86, CD83 and HLA-DR under the influence of EP, while CD11c expression and viability of DC are not affected. Furthermore, EP-treated DC restrain proliferation and modulate cytokine production of allogeneic lymphocytes. These results demonstrate that EP has the ability to direct DC towards tolDC.